2013
DOI: 10.1371/journal.pone.0079708
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Enhances the Proliferation of Non-Tumorigenic and Malignant Mammary Epithelial Cells through Increased leptin/IGF1R Signaling and Activation of AKT/mTOR

Abstract: Obesity and diabetes are associated with increased breast cancer risk and worse disease progression once cancer is diagnosed; however, the exact etiology behind these observations remains to be fully elucidated. Due to the global obesity/diabetes pandemic, it is imperative to understand how these diseases promote and enhance breast cancer and other common cancers. In this study we demonstrate that hyperglycemia promotes breast cancer by altering leptin/IGF1R and AKT/mTOR signaling. To our knowledge, we show fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
(56 reference statements)
2
36
0
Order By: Relevance
“…[1820] In addition, hyperglycemia characterized with diabetes directly or indirectly promotes IGF-1R phosphorylation (activation) by stimulating advanced glycation end product production to facilitate tumor cell proliferation. [21,22] Our results indicated that IGF-1R may mediate the mechanism of PTC carcinogenesis in diabetes.…”
Section: Discussionmentioning
confidence: 66%
“…[1820] In addition, hyperglycemia characterized with diabetes directly or indirectly promotes IGF-1R phosphorylation (activation) by stimulating advanced glycation end product production to facilitate tumor cell proliferation. [21,22] Our results indicated that IGF-1R may mediate the mechanism of PTC carcinogenesis in diabetes.…”
Section: Discussionmentioning
confidence: 66%
“…Leptin, an adipocyte-derived cytokine, would arouse proliferation in some cell types, such as mammary epithelium, which has an effect on the neoplasm cell proliferation, apoptosis, and cell cycle 205-207. Data has shown that high glucose levels can induce leptin signaling directly 208. Additionally, adiponectin in given cells may inhibit proliferation promoting apoptosis through the adenosine monophosphate kinase (AMPK) and MAPK pathways 180.…”
Section: Adipose Cellsmentioning
confidence: 99%
“…Initially, elevated levels of glucose serve as an efficient energy source and have been reported to increase cell proliferation, foster wound healing and mediate a switch from oxidative phosphorylation to glycolysis [139], [140] and [141]. However, these effects appear to be tissue specific, with much of the literature suggesting apoptotic effects with increasing levels of glucose [142] and [143].…”
Section: Glucose Metabolism and Insulin Resistance Post-burnmentioning
confidence: 99%